2006
DOI: 10.1029/2005jb003861
|View full text |Cite
|
Sign up to set email alerts
|

Volcano‐earthquake interaction at Mauna Loa volcano, Hawaii

Abstract: [1] The activity at Mauna Loa volcano, Hawaii, is characterized by eruptive fissures that propagate into the Southwest Rift Zone (SWRZ) or into the Northeast Rift Zone (NERZ) and by large earthquakes at the basal decollement fault. In this paper we examine the historic eruption and earthquake catalogues, and we test the hypothesis that the events are interconnected in time and space. Earthquakes in the Kaoiki area occur in sequence with eruptions from the NERZ, and earthquakes in the Kona and Hilea areas occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 58 publications
4
64
0
1
Order By: Relevance
“…Although the average perturbations of the hypocentral relocation are relatively small, we found that some earthquake clusters, previously addressed by various studies [Klein et al, 1987;Denlinger and Okubo, 1995;Gillard et al, 1996;Endo, 1985;Walter and Amelung, 2006] have spatial correlations with the resolved velocity structures and connections with geodetic flank motions (Figure 11). We infer that the relationships between seismicity and volcanic structure might provide us with a better understanding of volcano-tectonic processes.…”
Section: Seismicity and Velocity Structurementioning
confidence: 64%
See 2 more Smart Citations
“…Although the average perturbations of the hypocentral relocation are relatively small, we found that some earthquake clusters, previously addressed by various studies [Klein et al, 1987;Denlinger and Okubo, 1995;Gillard et al, 1996;Endo, 1985;Walter and Amelung, 2006] have spatial correlations with the resolved velocity structures and connections with geodetic flank motions (Figure 11). We infer that the relationships between seismicity and volcanic structure might provide us with a better understanding of volcano-tectonic processes.…”
Section: Seismicity and Velocity Structurementioning
confidence: 64%
“…However, seismic activity is substantial within and beneath the southeast flank of Mauna Loa (Figure 11), particularly in the low-velocity regions referred to as the Kao'iki and Hilea seismic zones [Endo, 1985]. The deeper earthquakes in these seismic zones (9 -13 km) form a background of seismicity, with larger earthquake magnitude, in contrast to the shallow seismic events [Thurber et al, 1989;Walter and Amelung, 2006]. This observation suggests that the deep earthquakes have a volcano-tectonic rather than magmatic origin [Koyanagi et al, 1988[Koyanagi et al, , 1989Jackson et al, 1992], i.e., due to seaward sliding of Mauna Loa's volcanic edifice over a basal decollement zone [Endo, 1985].…”
Section: Seismicity At Mauna Loa Volcanomentioning
confidence: 99%
See 1 more Smart Citation
“…The stress variation analysis has been successfully adopted also in a volcanic context, to study the interaction among sources of different nature: magma chambers, dykes, faults [67][68] [50]. Though these analyses are always conducted a posteriori, after the event occurrence, they contribute to support the stress-transfer reliability.…”
Section: Interactions Between Sourcesmentioning
confidence: 99%
“…In the case of volcanic triggering by unclamping of the magmatic chamber, variations of 0.1 bar have been demonstrated to be influential on the eruptive processes, while the lower value (0.01 bar) is a reasonable threshold to infer a moderate influence from a conservative hazard estimation point of view [58][59][60][61]. Note that a global agreement about the exact values of stress separating triggering from not triggering does not exist and therefore the exact values for our intervals were determined by expert judgment based on our experience and bibliography.…”
mentioning
confidence: 99%